All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 77549 by BK last updated on 07/Jan/20
Commented by abdomathmax last updated on 08/Jan/20
∫01dz1−xyz=∫01(∑n=0∞xnynzn)dz=∑n=0∞xnyn×1n+1⇒∫01(∫01dz1−xyz)dy=∑n=0∞xn×1(n+1)2⇒∫01(∫01(∫01dz1−xyz)dy)dx=∫01(∑n=0∞xn(n+1)2)dx=∑n=0∞1(n+1)3=∑n=1∞1n3=ξ(3)
Commented by BK last updated on 08/Jan/20
thanks
Terms of Service
Privacy Policy
Contact: info@tinkutara.com